KAJIAN TERHADAP AKAD MURABAHAH DENGAN KUASA MEMBELI DALAM PRAKTEK BANK SYARIAH - Wahyu Muhammad, Danang; Vivin Setyoningsih, Erika (Fakultas Hukum Universitas Muhammadiyah Yogyakarta, 2018)
Murabahah is a buying and selling contract between two parties in which the first party, the seller (bai’) has an obligation to sell goods needed by customers. The second party is the buyer (musytari). This party is obliged to pay the goods purchased. In murabahah, the first party or the seller (bai’) informs the customers about the cost of goods sold along with the agreed profit. Murabahah is commonly used in Islamic bank financing practices especially murabahah with buying authority. In this practice, akad (contract) murabahah and authorization contract are merged in one contract. This means that the seller will automatically become the party who gives authorization and the buyer becomes the party who receives authorization. The problem of the research is how the murabahah contract with buying authority is applied in Islamic bank financing which accords with Islamic principles. The type of the research is juridical normative by using legal approach. This research used primary, secondary, and tertiary legal materials as the main source. The analysis method used was descriptive method. The research result indicates that the merging of both murabahah contract and buying authority contract are approved to be correct according to Islamic principles. However, it must be conducted carefully since there has to be clear differentiator between when the murabahah contract and when authorization contract take place. Other than that, there has to be clear from several parties between the rights and obligations of the parties involved in murabahah contract and buying authority. In the financing practice with buying authority, banks are the seller when murabahah contract takes place and customers are the buyers. Meanwhile, in buying authority contract, banks are the principals and customers are the agents. Murabahah contract is conducted after buying authority contract takes place.